Modeling and experimental validation of a 2D electro-hydraulic servo proportional valve by bond graph - Hao Xu; Feixiang Jin; Tingbo Hou; Wangpiao Lin; Dexun Zhang (Advances in Mechanical Engineering)
The two-dimensional (2D) valve, which integrates the pilot and power stages into the spool, offers large flow and high power-to-weight ratio, making it widely used in military and aerospace applications. However, existing 2D valve models based on linear theory struggle to capture its nonlinear characteristics and are limited to specific steady-state conditions. This paper presents the development of a bond graph model for a 2D electro-hydraulic servo proportional valve (2D-EHSPV), which accounts for nonlinear factors such as magnetic hysteresis, Coulomb friction, and flow force. The bond graph model concretely illustrates the energy transfer relationships among the electro-mechanical converter (EMC), magnetic coupling (MC), and the 2D valve body, exemplifying the working principle of a two-dimensional pilot. The accuracy of the bond graph model was validated by comparing its dynamic analytical results with experimental data, demonstrating a high degree of accuracy with errors within 6.25%, which can serve as a theoretical foundation for 2D-EHSPV development. Building upon this model, the influence of key structural parameters on stability, energy efficiency, and feedback accuracy is analyzed using Matlab/Simulink. The bond graph model developed in this paper provides a theoretical basis for fault diagnosis, structural optimization, and control strategy development of other 2D valves.